Improving cranial ultrasound scanning strategy in neonates. Issue 1 (5th April 2016) - Bray, Lisa
Abstract : Cranial ultrasound scans are undertaken in this tertiary neonatal intensive care unit by the doctors within the department. A quality improvement project was undertaken by means of two PDSA cycles to determine adherence to neonatal cranial ultrasound scanning schedule, assess the quality of scan reporting, and formulate a comprehensive guideline outlining best practice. The baseline measurements assessed 93 scans of preterm infants and 9 of term infants. The results of this prompted intradepartmental education (PDSA cycle 1) then creation and implementation of a documentation template, a local guideline, and education via presentations, posters, and email (PDSA cycle 2). These encompassed 77 preterm and 5 term scans. In our baseline measurements, 52% of preterm infant scans and 44% of term infant scans were performed to schedule. Of premature baby scan reports, 75% had the time documented and 92% the name of the scanning doctor. After implementing changes PDSA cycle 2 data showed that 74% of preterm infant scans and all term infant scans were performed according to schedule, with 100% having the doctor's name and time of scan documented. We successfully introduced a guideline and documentation template, improving performance to schedule and documentation in most areas. It remains an ongoing challenge to adhere to basic standards of documentation; a template can assist in achieving this. Rotating trainees may offer insight into areas that could benefit from quality improvement. This enthusiasm can be successfully harnessed to implement changes to improve quality of patient care.